The attention to educational special needs at the University of Huelva on the Service-Learning and Mentoring - Mirian Hervás Torres; Adnaloy Pardo Rojas (Universidad de La Rioja, 2019)
This evaluative investigation describes research process which analyzes an intervention experience carried out at the Faculty of Education Psychology and Sports Sciences at the University of Huelva, in order to give an educational response to the needs presented by the students, diagnosing their needs, analyzing, designing, organizing and executing those actions that are necessary to facilitate them access to the curriculum. Framed in the alternative methodologies of Service-Learning and mentoring, students with or without functional diversity, had option to participate as mentors in the program. Participated 41 students, 5 did it as mentors and 36 were students who presented functional diversity. Through the mentor's notebook, academic performance, social skills, motivation, and commitment were assessed, while satisfaction was assessed by the satisfaction questionnaire. The intervention consisted of completion a training course for mentors and the development of 10 group mentoring sessions. The results indicate improvements in academic performance, skills and competencies of the participating students. Therefore, it can be established that participation has had a positive effect, providing a pedagogical response to the needs of students, and confirming the effectiveness of these methodologies.